DIAMOND-CONTAINING POLYCRYSTALLINE COMPOSITE MATERIALS AND METHODS OF THEIR PRODUCTION - Соколов, Олександр; Гаргін, Владислав (SWorldJournal, 2024)
This text discusses the production of diamond polycrystalline materials, factors that contribute to the strength of the diamond-diamond bond, conditions for forming a dense and finely dispersed material structure, and the resulting composite with improve